Black TiO2 Synthesis by Chemical Reduction Methods for Photocatalysis Applications - Andronic, Luminita; Enesca, Alexandru (Frontiers in Chemistry, 2020)
Applications of TiO2 nanomaterials in photocatalysis, batteries, supercapacitors and solar cells, have seen widespread development in recent decades. Nowadays, black TiO2 have won attention due to enhancing the solar light absorption by the formation of oxygen vacancies and Ti3+ defects, to promote the separation of photo-generated charge carriers leading to the improvement of the photocatalytic performance in H2 production and pollutants degradation. The enhanced photocatalytic activity of black TiO2 is also due to a lattice disorder on the surface and the presence of oxygen vacancies, Ti3+ ions, Ti-OH and Ti-H groups. Enhancing the optical absorption characteristics of TiO2 and change of energy level and band-gap of materials have been successfully demonstrated to improve their photocatalytic activities, especially for black TiO2 nanoparticles, which promote visible light absorption. The current review focuses on the investigation of the chemical reduction synthetic route for black TiO2 nanomaterials, and their proposed association with green applications such as photodegradation of organic pollutants and photocatalytic water splitting. The synthesis methods of black TiO2 involves the changes from Ti4+ to Ti3+ state, into different strategies: (1) The use of highly active hydrogen species such as H2, H2/Ar or H2/N2 gases, and metal hydrides (NaBH4, CaH2), (2) the reduction by active metals such as aluminum, magnesium and zinc, and (3) organic molecules such as imidazole and ascorbic acid.